ULTRASTRUCTURAL CHANGES OF CORTICOTROPIC ADENOCYTES OF HYPOPHYSIS AT LONG-TERM EXPOSURE OF RED SLUDGE - I.N. ROZHKOV; G.G. BORETSKY (Avicenna Tajik State Medical University, 2017)
Objective: The study of the features of ultrastructural changes and the character of the reparative processes in corticotropic cells (CC) of adenohypophysis exposure of red sludge. Methods: A study of the ultrastructural organization of the CC of hypophyses of the laboratory rats was carried out on an electron microscope GEM-100CX (Japan). To determine ultrastructural regularities of CC, the morphometric processing of the electron diffraction patterns was carried out on the computer image analyzer IBAS-2000 of OPTON Company (Germany). The concentration of adrenocorticotropic hormone (ACTH) was determined by a «two-step» enzyme immunoassay method for measuring the biologically active molecule of ACTH using the Biometrica test kit (USA). Results: Compared with control animals, in the conditions of exposure of red sludge in 14-day-old rats in the CC of the adenohypophysis, the nuclei indicate an increase in chromatin area, and in the cytoplasm - the amounts of the mitochondrion, secretory granules and its activity. However, in individual CCs, hyperchromium, corrugation and oedema of the nuclei are observed, in the cytoplasm - the vacuolization of the endoplasmic reticulum with partial destruction of its membranes and the formation of cavities, as well as compaction of the mitochondrial matrix. In 45-day-old animals, a reduction amount of chromatin is observed in the nuclei, and mitochondrion and secretory granules in the cytoplasm. In the ultrastructural organization of the majority of CC, the expressed dystrophic and destructive changes are revealed. On the 180th day of the action of red sludge with the simultaneous decrease in the morphometric indices of the CC and increasing in cells the evidence of dystrophic changes, the signs of regeneration have emerged (scale up the size and amount of the elements of the Golgi complex, the granular endoplasmic reticulum, young forms of mitochondrion, free ribosomes and polyribosomes). Conclusion: Reliably in the experiment the influence of red sludge on the ultrastructural organization of CC in the entryway part of hypophysis the temporal dependence effectiveness of adaptive reactions are placed. Maximum tension of mechanisms of adaptation was mentioned in the early period of exposure of red sludge. The inconsistency of adapt-accommodative mechanisms on the 45th day of the experiment was probably connected with the depletion of compensatory mechanisms. The regenerative-compensatory changes in CC in distant deadlines of the experiment proposes the possibility of adaptive regeneration in the time span.